Stakeholder Engagement Based Moral Hazard Analysis Model in FPSO-Tanker Oil Transfer - Palippui, Habibi; Rosyid, Daniel M.; Silvianita; Sade, Juswan (Emerging Science Journal, 2025)
This study aims to address moral hazard risks in FPSO-tanker oil transfer operations by introducing a semi-quantitative model rooted in stakeholder engagement theory. The model, named SEMHAM (Stakeholder Engagement-based Moral Hazard Analysis Model), incorporates four engagement indicators to calculate the total involvement percentage (PTI): Occurrence Frequency Value (OFV), Responsibility Weight Value (RWV), Critical Role Value (CRV), and Process Impact Value (PIV) to calculate the Total Involvement Percentage (PTI). This metric quantifies the behavioral influence of each stakeholder in the offloading process. Using operational data from 17 offshore zones based on Pertamina's 2023 report, eight primary stakeholder roles were evaluated using a weighted activity matrix. The findings indicate that FPSO Crew and Ship Crew possess the highest PTI scores, signifying greater control and potential risk, whereas administrative actors such as agents and port authorities were identified as lower-risk participants. The SEMHAM model facilitates risk classification and recommends appropriate digital oversight, including IoT-based monitoring, smart contracts, and role-based dashboards. This approach enables the integration of behavioral risk metrics into digital governance systems, thus supporting real-time operational monitoring. The model also demonstrates potential scalability to more complex offshore energy domains, such as LNG terminals and deepwater operations, enabling broader stakeholder governance beyond the current FPSO-tanker context.